Digital Transformation in Increasing the Effectiveness and Efficiency of Zakat Management Muhammadiyah Experience - Pamungkas, Puput Puspita Ganjar (STAI AL-FALAH CICALENGKA, 2023)
One of the efforts that can be made to reduce the number of poverty and other social inequalities in the community can be through philanthropic institutions that have credible, trusted and professional values in their management so that they can give birth to a prosperous society. However, it is undeniable that in Indonesia there are still people who avoid the obligation to pay zakat or doubt existing philanthropic institutions. This research provides an overview of philanthropic strategies and innovations under the auspices of the Muhammadiyah organization, namely LAZISMU, which is one of the largest philanthropies in Indonesia. The transparent management of Zakat, Infaq and Shodaqoh is continuous and fair, making all muzakki have high loyalty and trust in entrusting their property. The methods used are qualitative and relevant literacy studies. Keywords: Transformation, Effectiveness, Efficiency, Muhammadiyah Abstrak Salah satu upaya yang dapat dilakukan untuk mengurangi jumlah kemiskinan dan kesenjangan sosial lainnya di masyarakat dapat melalui lembaga filantropi yang memiliki nilai kredibilitas, terpercaya dan profesional dalam pengelolaannya sehingga dapat melahirkan masyarakat yang sejatera. Namun, tak dapat dipungkiri bahwasanya di Indonesia masih terdapat masyarakat yang mengindar dari kewajiban membayar zakat ataupun meragukan lembaga filantropi yang ada. Penelitian ini memberikan gambaran terkait strategi dan inovasi filantropi di bawah naungan organsasi Muhammadiyah yakni LAZISMU yang merupakan salah satu filantropi terbesar di Indonesia. Pengelolaan Zakat, Infaq dan Shodaqoh yang transaparan, bersifat kontinyu dan berkeadilan menjadikan seluruh muzakki memiliki loyalitas tinggi serta kepercayaan menitipkan hartanya. Metode yang digunakan ialah kualitatif dan studi literasi yang relevan. Kata kunci: Transformasi, Efektifitas, Efisiensi, Muhammadiyah